My love story ebook - Turner, Tina (2018)
In this New York Times bestseller, Tina Turner—the long-reigning queen of rock & roll and living legend—reveals personal stories she's never told before in print or film, about her complicated relationship with her mother, the tragic death of her son, and finally finding true love with Erwin, setting the record straight about her illustrious career in this eye-opening and compelling memoir. From her early years in Nutbush, Tennessee to her rise to fame alongside Ike Turner to her phenomenal success in the 1980s and beyond, Tina candidly examines her personal history, from her darkest hours to her happiest moments and everything in between. My Love Story is an explosive and inspiring story of a woman who dared to break any barriers put in her way. Emphatically showcasing Tina's signature blend of strength, energy, heart, and soul, this is a gorgeously wrought memoir as enthralling and moving as any of her greatest hits.